NAVIGATING ENTERPRISE DIGITALIZATION IN INDONESIA: INSIGHTS FROM A TECHNOLOGY-ORGANIZATION-ENVIRONMENT FRAMEWORK - Zaenal Aripin; Nyoman Dwika Ayu Amrita; Diah Fatma Sjoraida (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The digitalization of companies in Indonesia is a phenomenon that is receiving great attention in line with the acceleration of digital transformation in the industrial era 4.0. In this context, the Technology-Organization-Environment (TOE) Framework becomes important to understand the impact of technology, organizational factors and the external environment on the digitalization process. This article analyzes the role of digital technology in changing business strategies and company operations in Indonesia, as well as organizational and external environmental factors that become obstacles or opportunities in adopting digitalization. First, digital technology has influenced business strategy by enabling market expansion through e-commerce platforms, increasing operational efficiency through integrated management systems, and driving innovation in new products and services. However, organizational challenges such as limited skilled human resources, lack of management awareness of the strategic value of digitalization, and technology incompatibility with existing business processes are the main obstacles to technology adoption. Second, the external environment, especially government policies and market dynamics, plays an important role in shaping the challenges and opportunities in enterprise digitalization. Government policies that support technological innovation such as the Smart City program and national digital infrastructure can facilitate technology adoption. However, challenges arise from complex regulations regarding data security and privacy protection, as well as economic uncertainty that can hinder investment in technology. By analyzing TOE, this article provides comprehensive insight into how companies in Indonesia can navigate digital transformation. Practical suggestions include increased investment in developing skilled human resources, top-level management commitment in designing a digital vision, an organizational culture that is responsive to change, collaboration with the startup ecosystem and research institutions, and a focus on compliance with data security regulations.